Discovery of Divergent, Light-Controlled Catalysis Triggered by Ligand Photodissociation from Cobalt Complexes - Vystavkin, Nikita; Barday, Manuel; Teskey, Christopher J. (Synthesis, 2023)
Photochemistry has become a key area of research in synthetic chemistry over the last few decades. More recently, interest has grown in merging this area with transition metal catalysis to develop new reactivity. One key photoinduced step in this context is ligand dissociation from transition metal complexes. This has been used to develop light-gated catalysis, allowing for on/off control over a reaction. However, this concept can only result in a single product outcome. Our group has focused on the development of cobalt-catalyzed reactivity switches, enabled by a simple photodissociation step, which promotes one mechanistic path or another. As such, we can use a single catalytic platform to yield two different outcomes depending on whether the reaction is irradiated with light or not. This short review will focus on works in this area by our group and others.1 Introduction2 Photocontrolled Hydroboration3 Hydrogenation and Hydroformylation4 Conclusion
Keywords: cobalt; catalysis; photochemistry; photoswitching; hydroboration